Expression of hsa-let-7b-5p, hsa-let-7f-5p, and hsa-miR-222-3p and their putative targets HMGA2 and CDKN1B in typical and atypical carcinoid tumors of the lung - Pietro Di Fazio; Moritz Maass; Silvia Roth; Christian Meyer; Joana Grups; Peter Rexin; Detlef K Bartsch; Andreas Kirschbaum (Tumor Biology)
Typical and atypical carcinoid tumors belong to the neuroendocrine lung tumors. They have low recurrence and proliferation rate, lymph node, and distant metastases. Nevertheless, these tumors have shown a more aggressive behavior. In the last years, microRNAs were screened as new tumor markers for their potential diagnostic and therapeutic relevance. The expression of hsa-let-7b-5p, hsa-let-7f-5p, hsa-miR-222-3p, and their targets HMGA2 (high-mobility group A2) and CDKN1B (cyclin-dependent kynase inhibitor 1B, p27 kip1 ) was evaluated in this rare small group of patients. We analyzed the clinical data of all typical and atypical carcinoid tumors of patients who underwent surgical operation at Marburg University Hospital (n = 18) from 2000. Quantitative reverse transcription polymerase chain reaction was performed in formalin-fixed paraffin-embedded tumor tissue versus four tumor-free lung tissue samples. HMGA2 was stable or downregulated; only one patient showed a significant overexpression. CDKN1B showed a significant overexpression or a stable level; it was downregulated in two samples only. Hsa-miR-222-3p resulted almost stable or overexpressed except for two samples (significantly downregulated). Hsa-let-7f-5p was stable or overexpressed in the majority of analyzed samples, whereas hsa-let-7b-5p was significantly downregulated. HMGA2 and CDKN1B are differently expressed between atypical and typical carcinoid tumors, thus representing valid biomarkers for the classification of the two tumor groups. Hsa-let-7f-5p and HMGA2 are inversely correlated. Hsa-miR-222-3p does not correlate with its predicted target CDKN1B.